The Feasibility of Assessing Parent and Child Letter Knowledge in At-Rrisk Families Within a Museum Enrichment Setting - (:unkn) unknown (My University, 2017)
ABSTRACT THE FEASIBILITY OF ASSESSING PARENT AND CHILD LETTER KNOWLEDGE IN AT-RISK FAMILIES WITHIN A MUSEUM ENRICHMENT SETTING by Jeny Sara Thomas The University of Wisconsin-Milwaukee, 2017 Under the Supervision of Professor John Heilmann Purpose. This study addressed alphabet knowledge with children/parents who may be at-risk using a museum environment. The purpose of this study was to investigate whether the parent- and child-level assessments developed were appropriate to measure letter knowledge and children’s home literacy environment (HLE) from at-risk families and implement a museum enrichment program for the children/parents within a museum experience. Methods. Fourteen parent-child dyads from the Family Focus program of the Betty Brinn’s Children’s museum (BBCM) participated in this study. Each participating child was between 2;6 and 4;0 years of age. The participating parent-child dyads were randomly assigned to either the treatment or control. Both the treatment and control families completed a total of four visits to the museum. The treatment group parents were asked to implement a letter learning experience with their child in a natural way while exploring the museum. Whereas the control group parents were instructed to interact with their child at the museum as they normally would. Data was collected during the family’s first (baseline data) and fourth (post-treatment) museum visits. Two parent-level tests (which included background information questionnaire and parent interview questionnaire) and three child-level tests (which included the Upper-Case Alphabet Recognition subtest of the Phonological Awareness Literacy Screening for Preschool (PALS-PreK) test), an informal letter-recognition and letter-sound relationship task) were administered during the family’s first and fourth museum visits. Families were periodically called and emailed to follow up on their visits and experience at the museum. Results. This study followed a descriptive and experimental design. The descriptive design described the overall performance of the participants in parent-level and child-level tasks and to determine if the measures used for the study was developmentally appropriate for families who are at risk. The experimental design analyzed the presence or absence of significant differences between the treatment and control group families at the baseline and to compare the change in performances across the two groups over time with treatment. Conclusion. Based on the overall statistical analysis of the baseline data, the parent-level measures developed for the study were found to be appropriate for examining parent’s use of strategies and the child’s HLE among the at-risk families. Similarly, the baseline child level-measures were found to be appropriate for examining the letter knowledge skills of children from at-risk families. Additionally, the comparison between the baseline and post-treatment, parent- and child-level scores revealed no significant change in the scores of the control group families over time, with the implementation of the enrichment program.
Keywords: Assessment; Emergent Literacy; Letter Knowledge; Low Socioeconomic Status; Museum-Based Enrichment; Reading and Writing Development